ARE THERE NON–MOTOR SYMPTOMS SPECIFIC TO PARKINSON'S DISEASE?. Issue 11 (9th October 2013) - Steiger, Malcolm; Wong, Sui; Crossley, Joanne; Fletcher, Nick; Baker, Gus; Wieshmann, Udo
Abstract : Objective: Non–motor symptoms are increasingly recognised in Parkinson's disease contributing to the morbidity and disability. Are non–motor symptoms specific to PD, and can we identify which they are, or are they a feature of other chronic neurological conditions? Backgound: The non–motor symptoms of Parkinson's disease (PD) occur frequently, and are often under recognised, yet may have a significant impact on quality of life. Design/Methods: We performed an observational case–control questionnaire study comparing patients with Parkinson's disease, epilepsy, and spouse/carers controls. Three validated questionnaires were used. The Non–motor Symptoms Questionnaire (NMSQuest); Hospital Anxiety and Depression Scale; Liverpool Adverse Events Profile Scale (AEP). The control group of spouse/carers also completed the Scale of Quality of Life of Care–Givers. Other information collected included age, gender, disease duration, Hoehn & Yahr (for PD patients), and Liverpool Epilepsy Impact Scale for epilepsy patients. Patients were recruited from the regional Movement and Epilepsy clinics. Patients with cognitive impairment were excluded (MMSE<24). Results: Completed questionnaires were received from 129 PD, 60 epileptic patients, and 140 spouse/carer controls. Non–motor symptoms total scores were significantly higher in PD patients than epileptics when controlling for age, sex and duration of disease (p<0.05). There was no significant difference between the patient groups for anxiety and depression and the total AEP score.In individual items on the NMSQuest, constipation, incontinence, delusions and hallucinations, dreams, insomnia and sweating did not differ between the patient groups. Whilst restless legs, acting out dreams, memory, dribbling, and bladder urgency were highly significantly worse in the PD patients compared to epileptics (p<0.001).The patients had a significantly worse score on the NMSQuest compared to spouse/carers for all items except insomnia and swelling. Conclusion: Non–motor symptoms are a feature of PD, and are more common and more frequent than in patients with epilepsy and spouse/carers. In other chronic neurological conditions non–motor symptoms may occur. However, in PD patients certain non–motor symptoms and their severity appear to characterise the condition and may significantly impact on quality of life.